Sistem Pakar Diagnosa Penyakit Tht Berbasis Web Dengan Menggunakan Metode Certainty Factor - Munahar Muktar; Mulia Rahmayu; Budi Sudrajat (Universitas Pradita, 2020)
In the area of East Jakarta, especially in the Medika Clinic, the public can examine the initial symptoms of ENT. With the initial inspection that must be queued, can cause a long time. As a result, many people who do not know clearly the type of illness suffered and how to treat it. Because ENT disease is very related to organs where if not treated immediately, it will be difficult to move daily, therefore, the need for diagnosis of complaints from patients. These patients can directly access the website of a website where patients can diagnose without having to go to a hospital or clinic. By comparing previous studies or literature reviews, the problem to be discussed is to add more symptoms and diseases, then a solution for the disease. So that the website to be made is more detailed and clear, the results of this research is to produce an expert system website that can easily examine the symptoms of the patient and provide the patient's illness and solutions to overcome the disease.